2016
DOI: 10.1080/21505594.2016.1164367
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-physiological adaptations confer wax mothGalleria mellonellaresistance toBacillus thuringiensis

Abstract: Microevolutionary mechanisms of resistance to a bacterial pathogen were explored in a population of the Greater wax moth, Galleria mellonella, selected for an 8.8-fold increased resistance against the entomopathogenic bacterium Bacillus thuringiensis (Bt) compared with a non-selected (suspectible) line. Defense strategies of the resistant and susceptible insect lines were compared to uncover mechanisms underpinning resistance, and the possible cost of those survival strategies. In the uninfected state, resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 52 publications
(35 reference statements)
3
79
0
Order By: Relevance
“…The level of insect resistance to B. thuringiensis as well as to many other pathogens is determined by the status of its innate immunity (Dubovskiy et al., ; Ma, Sarjan, Preston, Asgari, & Schmidt, ). One of the main parameters mediating the outcome of insect–bacteria interactions is the prevalence of lysozyme and lower molecular weight antimicrobial peptides (AMPs) (Hwang & Kim, ; Johnston & Rolff, ).…”
Section: Introductionmentioning
confidence: 99%
“…The level of insect resistance to B. thuringiensis as well as to many other pathogens is determined by the status of its innate immunity (Dubovskiy et al., ; Ma, Sarjan, Preston, Asgari, & Schmidt, ). One of the main parameters mediating the outcome of insect–bacteria interactions is the prevalence of lysozyme and lower molecular weight antimicrobial peptides (AMPs) (Hwang & Kim, ; Johnston & Rolff, ).…”
Section: Introductionmentioning
confidence: 99%
“…5 In this issue of Virulence, the authors of the article "Immuno-physiological adaptations confer wax moth Galleria mellonella resistance to Bacillus thuringiensis" utilized an artificial selection experiment to identify traits that lead to Bt resistance, focusing on several characteristics previously implicated in toxin resistance. 6 Following selection for Bt resistance over 20 generations, Dubovskiy et al first measured the expression of 15 genes with roles in immune, stress, and inflammation responses in both the midgut (site of toxin binding) and the fat body, which is an important metabolic and homeostatic organ in the body cavity that produces many stress and immune effectors. Comparison between larvae from susceptible and resistant lines showed that resistant larvae had significantly higher expression levels of an inducible metalloprotease inhibitor, which inhibits proteases that contribute to Bt toxin activation, 2 growth factors in the midgut, and slightly elevated expression of additional immune and stress response genes.…”
mentioning
confidence: 99%
“…a higher fecundity) and a decrease in the diversity of the gut microbiota. 20 Change in epigenetic patterns in a Galleria resistant line after 30 generations of selection.…”
Section: Repeated Infections Of Galleria Mellonella Withmentioning
confidence: 99%
“…The understanding of the tolerance mechanisms of Galleria to Bt-Cry biocides has improved significantly thanks to the resistance evolution model in Galleria 20,9 There is now a need to explore in detail the relative importance on the selected resistance phenotype of Cry toxins and the other virulence factors expressed by Bt during infection. 15 Another important issue raised by this work is whether similar phenomena occur in insect pests, which are of high economical importance, such as Plutella xylostella.…”
Section: Repeated Infections Of Galleria Mellonella Withmentioning
confidence: 99%
See 1 more Smart Citation